The major food trees of the Angola black-andwhite colobus (Colobus angolensis palliatus) in Diani Forest, Kenya - Jansson, Camilla (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
The Angola black-and-white colobus (Colobus angolensis palliatus) is a subspecies of Colobus angolensis inhabiting fragmented forests in coastal Kenya and Tanzania. C. angolensis is regarded as Least Concern in the red list of IUCN because its populations are abundant. However, the populations of C. a. palliatus are relatively isolated from each other and their habitats are constantly undergoing deforestation which makes this subspecies vulnerable to extinction. In 2001, the estimated number of Angola black-and-white colobus in Kenya was 3100 to 5000 individuals confined to the forests of the Kwale District. The Diani Forest is an unprotected forest in the district and has been highlighted as a key habitat for future Angola black-and-white colobus conservation. There are few observations on C. a. palliatus and to conserve this subspecies more information is needed.